Targetable S100–RAGE Signaling Mediates Intrinsic Trastuzumab Deruxtecan Resistance in Metastatic Breast Cancer - Wenjuan Dong; Shiruo Wang; Bill Chan; Matthew Vasquez; Johnny Z.M. Cui; James Sampson; Caitlin Sannes; Wei Yang; Akshjot Puri; Jenny Chang; Hong Zhao; Xiaoxian Li; et al. (Clinical Cancer Research, 2026)
Abstract Purpose: Trastuzumab deruxtecan (T-DXd) has improved outcomes in metastatic breast cancer; however, a substantial subset of patients experience early lack of clinical benefit that is not reliably predicted by routine clinicopathologic variables. In an institutional cohort of 109 T-DXd–treated metastatic lesions, HER2 expression level, estrogen receptor (ER)/ progesterone receptor (PR) status, Ki-67 index, and metastatic site were not significantly associated with response, highlighting the need to define mechanistic determinants of intrinsic resistance. Experimental Design: We performed spatial transcriptomic and proteomic profiling using NanoString GeoMx Digital Spatial Profiling on pretreatment bone, brain, and soft-tissue metastases from patients with clinical benefit (response) versus early progression (resistance) on T-DXd. Tumor (pan-cytokeratin+) and immune (CD45+) compartments were analyzed to link tumor architecture and region-resolved signaling states with therapeutic response. Candidate resistance pathways were functionally evaluated in HER2-positive breast cancer cell lines and in vivo metastasis models treated with T-DXd alone or combined with the RAGE inhibitor TTP488. Results: Spatial proteogenomics revealed recurrent upregulation of S100 family alarmins in resistant tumor regions, associated with activation of a RAGE-centered prosurvival signaling program characterized by ERK, AKT, and STAT3 phosphorylation. Pharmacologic RAGE inhibition enhanced T-DXd–induced apoptosis, restored drug sensitivity in vitro, and significantly reduced metastatic burden in lung and brain metastasis models. Conclusions: Spatial proteogenomics identifies a conserved S100-RAGE–driven survival state coupled to immune-excluded tumor architecture as a mechanism of intrinsic T-DXd resistance across metastatic niches. Targeting this pathway with an orally available RAGE antagonist restores T-DXd responsiveness and offers an immediately translatable strategy to overcome resistance in metastatic breast cancer.